2020
DOI: 10.1038/s41598-020-58674-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of anti-PD-1/PD-L1 inhibitors for the treatment of advanced or metastatic cancer: a systematic review and meta-analysis

Abstract: Anti-PD-1/PD-L1 inhibitors provide a survival advantage over conventional therapies for treatment of advanced or metastatic cancer. However, the factors determining which patients benefit the most from anti-PD-1/PD-L1 inhibitors are unknown, making treatment-related decisions difficult. We performed a systematic review and meta-analysis of acquired data to assess the efficacy and toxicity of anti-PD-1/ PD-L1 inhibitors in advanced and metastatic cancer. A thorough search strategy was applied to identify random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(122 citation statements)
references
References 57 publications
4
118
0
Order By: Relevance
“…New cancer-targeting compounds also include specific inhibitors of the cell cycle [e.g., cyclindependent kinase (CDK)-inhibitors; reviewed in (26)] or inhibitors of epigenetic regulators of cell differentiation and proliferation [e.g., inhibitors of enzymes modifying DNA or histones by methylation/acetylation; reviewed in (27,28)]. Moreover, PD-1/PD-L1 inhibitors in immunotherapy work as immune checkpoint inhibitors (ICIs) that target the tumor cells' ability to evade immune recognition and recently were described to be the preferable treatment option for a subset of patients with advanced or metastatic tumors (29).…”
Section: Molecular Targeted Therapies For Precision Oncologymentioning
confidence: 99%
“…New cancer-targeting compounds also include specific inhibitors of the cell cycle [e.g., cyclindependent kinase (CDK)-inhibitors; reviewed in (26)] or inhibitors of epigenetic regulators of cell differentiation and proliferation [e.g., inhibitors of enzymes modifying DNA or histones by methylation/acetylation; reviewed in (27,28)]. Moreover, PD-1/PD-L1 inhibitors in immunotherapy work as immune checkpoint inhibitors (ICIs) that target the tumor cells' ability to evade immune recognition and recently were described to be the preferable treatment option for a subset of patients with advanced or metastatic tumors (29).…”
Section: Molecular Targeted Therapies For Precision Oncologymentioning
confidence: 99%
“…), it might be promising to use drugs that can alter intercellular communication. Thus, compounds that activate interactions between the tumor and the patient's immune cells have shown their high efficiency [244,245]. Also, drugs that inhibit molecular mediators of intercellular communication are currently being actively investigated [246,247].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding specific markers, Matsuo et al found a higher expression of MDR1 in primitive ovarian cancers which then developed BMs and in the BMs themselves; this finding has therapeutic relevance, since a higher MDR1 expression is associated with resistance to chemotherapy drugs like paclitaxel [77]. Choi et al reported a higher PD-L1 expression in brain metastasis compared to primary tumors [71] with potential implications for immunotherapy [78]. Indeed, the immune system seems to play a significant role in shaping OC metastasis development: a higher expression of IL7R, probably related to T cells activation and infiltration, was found in OC metastases, as well as differences in CALB2, CYP1B1, EFTUD1, RARRES2 and TIMP3 expressions [79].…”
Section: Pathology and Molecular Profilingmentioning
confidence: 99%